2003
DOI: 10.1345/aph.1d090
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol in Severe Asthma with Premenstrual Worsening

Abstract: The administration of estradiol during the late luteal phase of the menstrual cycle to a woman with severe asthma with PMA was associated with improved asthma symptoms, pulmonary function, and peak expiratory flows, and lower serum eosinophil protein X and urinary leukotriene E(4) biomarker concentrations. Thus, estradiol's potential role in women with severe asthma and PMA may warrant further exploration in this subgroup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…underlying this susceptibility remains unclear. Ensom and colleagues demonstrated the beneficial effects of estradiol in a severely asthmatic woman with premenstrual worsening of asthma (24).…”
Section: Discussionmentioning
confidence: 99%
“…underlying this susceptibility remains unclear. Ensom and colleagues demonstrated the beneficial effects of estradiol in a severely asthmatic woman with premenstrual worsening of asthma (24).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported a reduction in asthma symptoms and corticosteroid requirement for asthma control in women with asthma who were given combined OC, estrogen, or gonadotropin releasing hormone analogue. 24,27,28,32,35 Because OC prevents luteinizing hormone surge and suppresses luteinizing hormone secretion, progesterone levels remain at a much lower level throughout the menstrual cycle in women taking OC compared with luteal phase levels of progesterone in women not taking OC. 11 Therefore, it is possible that the observed reduction in asthma symptoms with OC use may be a result of an absence of luteal phase increase in progesterone levels.…”
Section: Discussionmentioning
confidence: 99%
“…Changes occurring during sleep, in both non-rapid and rapid eye movement sleep stages, result in a shift from inhibitory to excitatory transmission to the AVPNs that could lead to worsening of airway function [Young et al 2005] (Figure 1). Similar mechanisms involving a decrease of tonic GABAergic inhibitory influences, may at least in part explain exercise- [McFadden and Gilbert, 1994] and premenstrual- [Ensom et al 2003] induced asthma. In the latter, it may involve a decrease of a GABA A receptor modulator, the 3-a-OH-dihydroprogesterone, which has an action similar to a neurosteroid.…”
Section: Central Mechanismsmentioning
confidence: 99%